The Effectiveness of Inventory Control Systems in Public Food Logistics: Evidence From Indonesia - Mutiara Balqis Adam; Siti Nursyamsiah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the effectiveness of a rice inventory control system in supporting the sustainability and stability of the national food supply. It evaluates key indicators, including planning accuracy, recording accuracy, compliance with standard operating procedures, stock availability and control, and the system’s ability to mitigate the risk of inventory damage. A descriptive qualitative approach with a case study design was employed, using both primary and secondary data. Primary data were collected through interviews with personnel directly involved in inventory management, while secondary data were obtained from document reviews such as SOPs, organizational structures, and inventory records. Data analysis involved data reduction, presentation, and conclusion drawing. The findings reveal that the inventory control system operates in a structured and integrated manner through the use of an ERP system, periodic stocktaking, and preventive as well as corrective quality control measures. However, increased absorption volume driven by government assignments poses challenges to warehouse capacity management. Overall, the system is considered effective in maintaining rice supply stability.